2020
DOI: 10.1051/0004-6361/202039529
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-nonthermal energy partition in solar flares derived from X-ray, EUV, and bolometric observations

Abstract: Context. In solar flares, energy is released impulsively and is partly converted into thermal energy of hot plasmas and kinetic energy of accelerated nonthermal particles. It is crucial to constrain the partition of these two energy components to understand energy release and transport as well as particle acceleration in solar flares. Despite numerous efforts, no consensus on quantifying this energy balance has yet been reached. Aims. We aim to understand the reasons for the contradicting results on energy par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 100 publications
(117 reference statements)
1
22
0
Order By: Relevance
“…High-resolution imaging observations provide rich information about details of the reconnection process which result from its internal dynamics, especially the formation of plasmoids 21 , 22 and turbulent structures 23 , and from the complexity and three-dimensional (3D) nature of the solar magnetic field 24 , 25 . Spectral and multi-wavelength data reveal aspects of the microscopic processes, e.g., particle acceleration 26 , 27 , the nonthermal-thermal energy partition 28 , the plasmoid instability 29 , 30 , and bursty 31 or turbulent reconnection 32 , 33 , in addition to flows 34 . Finally, besides hot flare plasmas, the Sun also allows the reconnection of cool chromospheric structures to be studied 24 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution imaging observations provide rich information about details of the reconnection process which result from its internal dynamics, especially the formation of plasmoids 21 , 22 and turbulent structures 23 , and from the complexity and three-dimensional (3D) nature of the solar magnetic field 24 , 25 . Spectral and multi-wavelength data reveal aspects of the microscopic processes, e.g., particle acceleration 26 , 27 , the nonthermal-thermal energy partition 28 , the plasmoid instability 29 , 30 , and bursty 31 or turbulent reconnection 32 , 33 , in addition to flows 34 . Finally, besides hot flare plasmas, the Sun also allows the reconnection of cool chromospheric structures to be studied 24 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…During solar flares, magnetic energy accumulated in the solar corona is explosively released via magnetic reconnection and converted in the form of particle acceleration, plasma heating, and bulk flows (Shibata & Magara 2011;Benz 2017). An enormous number of electrons can be accelerated to high energies (up to tens of MeV) and contain a significant fraction of the dissipated magnetic energy (Lin & Hudson 1976;Emslie et al 2012;Aschwanden et al 2017;Warmuth & Mann 2020). High-energy electrons can further produce hard X-ray (HXR) emission via the bremsstrahlung mechanism and microwave emission via the gyrosynchrotron mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In large flares, it has been shown that the injected nonthermal energy derived from RHESSI data is sufficient and even in excess to explain the thermal component of strong flares (Aschwanden et al 2017;Kleint et al 2016). However, it was shown that for weak flares, a deficit of energetic electrons to affect the low levels of the atmosphere in which the bolometric emission (NUV, white light, near-IR radiation) is initiated (Warmuth & Mann 2020). Inglis & Christe (2014), Warmuth & Mann (2020) reported an apparent deficit of nonthermal electrons in weak flares by computing the ratio of thermal energy (and losses) and energy in nonthermal electrons.…”
Section: Non-lte Radiative Transfer Modelsmentioning
confidence: 99%
“…However, it was shown that for weak flares, a deficit of energetic electrons to affect the low levels of the atmosphere in which the bolometric emission (NUV, white light, near-IR radiation) is initiated (Warmuth & Mann 2020). Inglis & Christe (2014), Warmuth & Mann (2020) reported an apparent deficit of nonthermal electrons in weak flares by computing the ratio of thermal energy (and losses) and energy in nonthermal electrons. The interpretation depends on where and in which area the electrons are accelerated.…”
Section: Non-lte Radiative Transfer Modelsmentioning
confidence: 99%